The effect of stormwater controls on sediment transport in urban streams - Rohrer, Christine A., author; Roesner, Larry A., author; Bledsoe, Brian P., author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
Urbanization of a watershed increases impervious area, and consequently increases stormwater runoff. When left uncontrolled, these increases in stormwater runoff cause downstream flooding, accelerate channel erosion, and impair aquatic habitat. Increases in the magnitude and duration of stormwater runoff that accompany uncontrolled development allow a stream to carry more sediment than it could prior to watershed development. When a watershed cannot supply the stream with the volume of sediment it has the capacity to carry, channel degradation may occur in the form of incision, lateral migration, or a combination of both. This study evaluates the potential impact of watershed development on sediment transport in a prototype headwater stream subjected to typical residential development. Event based and continuous simulations, using 50 years of hourly rainfall records were performed with two climatically different locales. The first in the semiarid climate of Fort Collins, Colorado and the other in a typical southeastern climate, Atlanta, Georgia. Five conditions were evaluated for the study watershed, including: current (undeveloped) conditions, fully developed conditions, without stormwater controls, and fully developed conditions with stormwater controlled using (a) the City of Fort Collins flood control standard, (b) the City of Fort Collins flood control standard and water quality capture volume (WQCV) criteria, and, (c) using common standards of practice in the United States: control of the 100- and 2-year storms to historic peak discharge rates and control of the WQCV. For each scenario examined, sediment transport potential is evaluated for two noncohesive soil types: medium gravel and medium sand.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.